Penerapan Terapi Murottal terhadap Tingkat Kecemasan Pasien Pre-operasi Sectio Caesarea (SC) di Ruang Gladiol RSUD Dr. Tjitrowardojo Purworejo - Rima Febtriani Khasanah; Despita Pramesti (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Background: Sectio Caesarea is a surgical procedure to create an artificial birth canal by making an incision in the uterine wall, allowing the baby to be delivered safely and healthily. C-section has psychological impacts such as fear, anxiety, and stress. Physiological effects include increased blood pressure, shortness of breath, palpitations, elevated heart rate, and difficulty sleeping. Spiritually, it requires support from the husband/family, prayer, dhikr, and listening to murottal. Anxiety is an emotional response related to feelings of worry, restlessness, and fear when facing dangerous or threatening procedures. The therapy used to provide relaxation, calmness, peace, and to uplift the spirit in facing upcoming situations is murottal therapy using Surah Ar-Rahman verse 78, which means “The Most Merciful” and is believed to soothe the soul and body. Objective: To overcome anxiety levels in second-time pregnant patients undergoing pre-operative C-section with murottal therapy using Surah Ar-Rahman. Method: This research used a case study of 2 second-time pregnant patients undergoing C-section, conducted on May 16 & 17, 2025, for 1 session of 30 minutes with murottal therapy from Surah Ar-Rahman verse 78 and the APAIS questionnaire for pre- and post-test. Results: Pre-test scores showed that Mrs. Y scored 22 and Mrs. R scored 17, with a mean pre-test score of 19.5, and a median post-test result of 8. Post-test scores showed Mrs. Y scored 9 and Mrs. R scored 7, indicating a decrease in anxiety level from severe to mild according to the APAIS score. Conclusion: The application of murottal therapy for pre-operative Sectio Caesarea patients can reduce anxiety in patients undergoing surgery.